Self-Assessment: The Role of the Social Environment - Armin Falk; Fabian Kosse; Hannah Schildberg-Hörisch; Florian Zimmermann (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This study presents descriptive and causal evidence on the role of the social environment in shaping the accuracy of self-assessment. We introduce a novel incentivized measurement tool to measure the accuracy of self-assessment among children and use this tool to show that children from high socioeconomic status (SES) families are more accurate in their self-assessment, compared to children from low SES families. To move beyond correlational evidence, we then exploit the exogenous variation of participation in a mentoring program designed to enrich the social environment of children. We document that the mentoring program has a causal positive effect on the accuracy of children's self-assessment. Finally, we show that the mentoring program is most effective for children whose parents provide few social and interactive activities for their children.
Keywords: D03; C21; C91; I24; 330; self-assessment; beliefs; experiments; randomized intervention; children